Efeitos de raça, idade e gênero sobre o plasma rico em plaquetas em equinos e correlação da contagem plaquetária com o aspecto físico - Paz, Letícia Bisso (2021)
Platelet-rich plasma (PRP) is a source of several growth factors and other molecules that participate in modulating the inflammatory response and tissue repair. In equine medicine, PRP has stood out for its beneficial action in the treatment of wounds, in addition to its use in several conditions in which inflammation reduction and tissue repair are needed. However, there are still intrinsic factors that differ between established protocols and can influence the quality of the final product. This study aimed to evaluate the effects of race, age and gender on equine PRP and to correlate its physical appearance with platelet count. Fifty blood samples were collected from animals of five different breeds (Thoroughbred - TB, Brazilian Sport Horses - BSH, Brazilian Criollo Horses - BCH, Miniature Horses - MH and Cross Breed horses - CB) for the preparation of PRP and they were investigated as to platelet concentration in relation to race, age and gender. In addition, a PRP physical analysis score was established to correlate its appearance with the platelet count. Cell count was performed by automatic and manual methods, while the physical analysis of the PRP was based on color, appearance and ability to separate blood components. MH had significantly higher platelet concentration than BSH (p < 0.05), but the other comparisons between breeds showed no difference in platelet count. There was no significant difference for gender but there was a weak correlation of age with PRP platelet concentrations (rs = -0.24). Most of the PRP presented yellow colour, the separation of blood components showed no correlation but the aspect showed a moderate correlation (rs = 0.30) with platelet count. Results suggest that PRP platelet concentration can be influenced by intrinsic factors such as breed. Additionally, the analysis of PRP aspect can help to evaluate the quality of the product, when there is no access to platelet counts.